Minimally invasive pediatric surgery: Our experience - Saravanan K; Kumaran V; Rajamani G; Kannan S; Mohan N; Nataraj M; Rangarajan R (Wolters Kluwer Medknow Publications, 2008)
Aim: Departmental survey of the pediatric laparoscopic and thoracoscopic procedures. Materials and Methods: It is a retrospective study from January 1999 to December 2007. The various types of surgeries, number of patients, complications and conversions of laparoscopic and thoracoscopic procedures were analyzed. Results: The number of minimally invasive procedures that had been performed over the past 9 years is 734, out of which thoracoscopic procedures alone were 48. The majority of the surgeries were appendicectomy (31%), orchiopexy (19%) and diagnostic laparoscopy (16%). The other advanced procedures include laparoscopic-assisted anorectoplasty, surgery for Hirschprung′s disease, thoracosocpic decortication, congenital diaphragmatic hernia repair, nephrectomy, fundoplication, etc. Our complications are postoperative fever, bleeding, bile leak following choledochal cyst excision and pneumothorax following bronchogenic cyst excision. A case of empyema thorax following thoracoscopic decortication succumbed due to disseminated tuberculosis. Our conversion rate was around 5% in the years 1999 to 2001, which has come down to 3% over the past few years. Conversions were for sliding hiatus hernia, nephrectomy, perforated adherent appendicitis, Meckel′s diverticulum, thoracoscopic decortication and ileal perforation. Conclusion: The minimally invasive pediatric surgical technique is increasingly accepted world wide and the need for laparoscopic training has become essential in every teaching hospital. It has a lot of advantages, such as less pain, early return to school and scarlessness. Our conversion rate has come down from 5% to 3% with experience and now we do more advanced procedures with a lower complication rate.